Empowering Dairy Farmers through Milk Producer Companies: A Review of Policies, Stakeholders and Extension Interventions - Sivasankar M; Anusuya K; Moulidharshan R; Nandha Kumar R; Shiva Reddy S V; Aarthi M; Savitha Gopalakrishnan (Archives of Current Research International, 2025)
India’s dairy sector, largely dominated by small and marginal farmers, remains vital for rural livelihoods but is hindered by structural challenges including fragmented landholding, low bargaining power, inadequate veterinary services and market inefficiencies. Despite contributing over 70% of the nation’s milk supply, these producers face high input costs, limited access to credit and technology and poor price realization. In response, Milk Producer Companies, a form of Farmer Producer Organizations has emerged as an effective institutional mechanism. MPCs consolidate farmers’ resources, enabling collective procurement, value addition and direct market engagement. Supported by government bodies such as SFAC, NABARD and NDDB, along with NGOs and private stakeholders, MPCs are bolstered through financial aid, capacity-building and infrastructure support. Extension services play a pivotal role in training, technology adoption and governance enhancement. Case studies like Shreeja and Karimnagar MPCs exemplify success in women empowerment, operational efficiency and sustainable growth. However, challenges such as fodder scarcity, limited financial inclusion, and weak governance persist. This review highlights the transformative potential of MPCs in reshaping India’s dairy economy through inclusive, market-driven and scalable models. Strengthening institutional support, promoting digital integration and fostering leadership are essential to ensuring MPCs become resilient, self-sustaining enterprises that uplift millions of rural dairy farmers.